EFEK PENYISIPAN Cu KE DALAM DYE BERAS HITAM DENGAN LUASAN 0,5 cm2 PADA DYE SENSITIZED SOLAR CELL (DSSC) - Ulfa Mahfudli Fadli; Ardimas; Agus Supriyanto; Cari; Ashari Bayu Prasada (Jurnal Matematika dan Sains (JMS), 2021)
Thanks to the addition of copper (Cu) metal into black rice (Oryza sativa L. indica) dye as an active material, It has been successfully developed Dye-Sensitized Solar Cells (DSSC). The structure of the sample as a sandwich consisting of the working electrode (TiO2), dye, electrode of platinum (Pt) and the electrolyte sandwiched between two electrodes. Extraction process of black rice Dye was stirred for 30 minutes, then mixed with copper metal (Cu) and be waited for 24 hours. Cu metal was obtained by stirring Copper Sulfate Pentahydrate for 2 hours. The Current and voltage (I-V) of the sample was characterized by using Keithley 2602A. The measurement results showed that the inserting Cu metal of 2 g (0.36 M) was reached the highest efficiency of 0.0217%.